Perancangan Alat Pemberi Makan Hewan Otomatis dengan Sensor Ultrasonik dan Teknologi Mikrokontroler - Tarrosa, Bayu Asta; Ramadhan, Bilal; Hafizh, Kemas M.; Anugrah, M. Rifky; Muslimin, Muslimin; Luqyana, Dhiya; Muhamad, Azam Milah (Manutech : Jurnal Teknologi Manufaktur, 2025)
Along with the advancement of technology and the increasing busyness of everyday people, the need for tools to help with daily activities is becoming increasingly important, including for pet owners such as cats. This study designs an automatic tool called "Zen-Feeder," which is an automatic pet feeding tool that uses a microcontroller and ultrasonic sensor to detect the presence of cats, provide food on a scheduled basis and according to the dosage so that owners can more freely manage their time and activities outside the home. The ultrasonic sensor detects the presence of cats around the feeding place, according to the characteristics of cats coming to the feeding place when it is time to eat. The tool's servo motor will automatically open the feeding valve when the cat is within a certain distance from the feeding place and release food with a predetermined dosage. Then, the valve will close again. In light of the growing demands of modern life, the development of the "Zen-Feeder" represents a significant advancement in pet care technology, offering convenience and peace of mind for cat owners by ensuring their pets are fed consistently and healthily, even in their absence.